MATURITY RATING OF INFORMATION TECHNOLOGY GOVERNANCE FOR STATE OWNED ENTERPRISES (SOE) - Yuthsi Aprilinda; Ayu Kartika Puspa; Fenty Ariani (International Conference on Engineering and Technology Development (ICETD), 2017)
This research is motivated by the importance of Information Technology Governance (IT Governance). It is necessary to know the absolute value of a company based on maturity level, it is necessary to know how to improve maturity model level, and control the performance of Human Resources (HR). The purpose of this research is to give the achievement level of maturity level of Domain Planning and Organization (PO) and Acquire and Implement (AI) as well as to provide solution from each level of maturity based on Cobit 4.1 framework using governance application information technology using the Cobit 4.1 framework. This study does not address the domains of Deliver and Support and Monitor and Evaluate. This research uses a qualitative approach. The application created in this writing is desktop-based application. In the manufacturing process required initial design of the application that is presented through the interface design. By using this application, it is expected to assist the management in controlling the existing technology and human resources infrastructure and the management can evaluate the current organizational maturity level position (as-is) and the future expectation (to-be).